Pharmacological Evaluation of Dotinurad, a Selective Urate Reabsorption Inhibitor - Taniguchi, Tetsuya; Ashizawa, Naoki; Matsumoto, Koji; Saito, Ryo; Motoki, Keisuke; Sakai, Miku; Chikamatsu, Noriko; Hagihara, Chiharu; Hashiba, Masamichi; Iwanaga, Takashi (The Journal of pharmacology and experimental therapeutics, 2019)
The effect of dotinurad [(3,5-dichloro-4-hydroxyphenyl)(1,1-dioxo-1,2-dihydro-3H-1λ6-1,3-benzothiazol-3-yl)methanone] was compared with that of commercially available uricosuric agents—namely, benzbromarone, lesinurad, and probenecid. Its effect on urate secretion transporters was evaluated using probe substrates for respective transporters. Dotinurad, benzbromarone, lesinurad, and probenecid inhibited urate transporter 1 (URAT1) with IC50 values of 0.0372, 0.190, 30.0, and 165 μM, respectively. Dotinurad weakly inhibited ATP-binding cassette subfamily G member 2 (ABCG2), organic anion transporter 1 (OAT1), and OAT3, with IC50 values of 4.16, 4.08, and 1.32 μM, respectively, indicating higher selectivity for URAT1. The hypouricemic effects of dotinurad and benzbromarone were evaluated in Cebus monkeys. Dotinurad, at doses of 1–30 mg/kg, concomitantly decreased plasma urate levels and increased fractional excretion of urate (FEUA) in a dose-dependent manner. On the contrary, benzbromarone, at a dose of 30 mg/kg, showed a modest effect on plasma urate levels. The inhibitory effect of dotinurad on urate secretion transporters was evaluated in Sprague-Dawley rats, with sulfasalazine and adefovir as probe substrates of ABCG2 and OAT1, respectively. Drugs, including febuxostat as a reference ABCG2 inhibitor, were administered orally before sulfasalazine or adefovir administration. Dotinurad had no effect on urate secretion transporters in vivo, whereas benzbromarone, lesinurad, probenecid, and febuxostat increased the plasma concentrations of probe substrates. These results suggested dotinurad is characterized as a selective urate reabsorption inhibitor (SURI), which is defined as a potent URAT1 inhibitor with minimal effect on urate secretion transporters, including ABCG2 and OAT1/3, because of its high efficacy in decreasing plasma urate levels compared with that of other uricosuric agents. Our study on the inhibitory effects on urate transport showed that dotinurad had higher selectivity for urate transporter 1 (URAT1) versus ATP-binding cassette subfamily G member 2 (ABCG2) and organic anion transporter (OAT) 1/3 compared to other uricosuric agents. In Cebus monkeys, dotinurad decreased plasma urate levels and increased fractional excretion of urate in a dose-dependent manner. To determine the inhibitory effect of dotinurad on urate secretion transporters, we studied the movement of substrates of ABCG2 and OAT1 in rats. Dotinurad had no effect on these transporters, whereas the other uricosuric agents increased the plasma concentrations of the substrates. These results suggested dotinurad as a potent and selective urate reabsorption inhibitor is characterized by increased efficacy with decreasing plasma urate levels.